Retrospective evaluation of acute kidney injury in dogs with pit viper envenomation (2008–2017): 56 cases. Issue 6 (24th September 2020) - Martinez, Jennifer; Londoño, Leonel A.; Schaer, Michael
Abstract: Objectives: To describe the clinicopathological characteristics of dogs that develop acute kidney injury (AKI) secondary to pit viper envenomation, and to describe the association between development of AKI and clinical course and outcome. Design: Retrospective study. Setting: University teaching hospital. Animals: Client‐owned dogs treated with at least 1 vial of antivenom following pit viper envenomation and that had at least 2 plasma creatinine concentrations measured during the course of hospitalization. Interventions: None. Measurements and Main Results: Sixty‐three dogs met the inclusion criteria. One was excluded due chronic kidney disease, and 6 were excluded due to nonsteroidal anti‐inflammatory drug administration. Of the 56 dogs included in the study, 16 developed AKI (29%). Dogs with AKI received a significantly higher dose of antivenom, 8.7 ± 6.8 total vials versus dogs in the non‐AKI group that received 4.2 ± 2.6 vials ( P  = 0.006). Dogs in the AKI group were significantly more tachycardic ( P  = 0.028), hypotensive ( P  = 0.002), had a higher shock index ( P  = 0.012), and were more likely to receive transfusions with packed red blood cells ( P  = 0.042) than dogs in the non‐AKI group. No significant association was identified between the development of AKI and length of hospitalization. The only factors that were significantly associated with degree of severity of AKI included the receipt of blood transfusion ( P  = 0.006) and number of vials of antivenom administered ( P  = 0.03). The development of AKI was significantly associated with outcome ( P  < 0.001), with 5 of 16 (31%) dogs in the AKI group surviving to discharge, 7 of 16 (44%) dying, and 4 of 16 (25%) being euthanized versus 39 of 40 (98%) surviving to discharge in the non‐AKI group and 1 of 40 (2%) dying in hospital. Conclusion: Development of AKI in dogs following pit viper envenomation carries an increased risk of mortality that is associated with severity of shock at presentation and increased doses of antivenom administration.